Các tritecpen oleanan từ cây bông ổi Lantana camara L. - Đậu và cộng sự, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
Three pentacyclic triterpenoids, Lantaden B (3), Icterogenin (4) and 3-oxo-25-methylhydroxy-22b-[(Z)-2’-butenoyloxy]-olean-12-ene-28-oic acid (5) and two common steroids, b-sitosterol (1) vµ b-sitosterol 3-O-b-D-glucopyranoside (2) were isolated from the aerial parts of Lantana camara L. Structures of the triterpenoids were elucidated by spectroscopic methods.